PENGUATAN PERAN GURU DI ERA DIGITAL MELALUI PROGRAM PEMBELAJARAN INSPIRATIF - Adang Sutarman; Cucu Atika (STAI Darul Qalam Tangerang, 2026)
The main problem raised in this paper is the need to review the role of teachers in learning in the digital era. This is based on two assumptions. On the one hand, teachers are considered to be the main learning resource and determinant of student achievement, on the other hand, the rapid development of science and technology in the current digital era makes access to student learning easier so that the role of teachers is only to transfer knowledge into marginalization. By analyzing the role of teachers in learning and the new paradigm of learning in the digital era, this paper offers a strategy to strengthen the role of teachers in the digital era in an effort to improve the quality of education through inspirational learning programs. Inspirational learning facilitates students to learn more than just knowing and understanding, but applying, making creations, and contributing. For this reason, designing inspirational learning with multistrategy is recommended so that students are able to adapt and optimally master competencies amid the current rapid development of science and technology.